2004
DOI: 10.1159/000077045
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron Intake and Iron Status of German Female Vegans: Results of the German Vegan Study

Abstract: Background: As shown in previous studies vegetarians and especially vegans are at risk for iron deficiency. Our study evaluated the iron status of German female vegans. Methods: In this cross-sectional study, the dietary intakes of 75 vegan women were assessed by two 9-day food frequency questionnaires. The iron status was analyzed on the basis of blood parameters. Results: Mean daily iron intake was higher than recommended by the German Nutrition Society. Still 42% of the female vegans <50 years (young women,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 21 publications
4
54
2
2
Order By: Relevance
“…Despite the health benefits that vegetarian and vegan-life style and dietary habits provide, such diets have been associated with iron deficiencies (Craig and Mangels, 2009). Waldmann et al (2004) investigated the iron deficiency in German vegan females and concluded that, although their average iron intake was above the recommended level, 40% of them were considered iron-deficient because of its poor absorption, and therefore, iron supplements were prescribed to them.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the health benefits that vegetarian and vegan-life style and dietary habits provide, such diets have been associated with iron deficiencies (Craig and Mangels, 2009). Waldmann et al (2004) investigated the iron deficiency in German vegan females and concluded that, although their average iron intake was above the recommended level, 40% of them were considered iron-deficient because of its poor absorption, and therefore, iron supplements were prescribed to them.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of dietary fibre increases the food volume without increasing the energy content, while binding relatively large amounts of water; this leads to directly increased satiety. Folate, iron and vitamin B12 are currently in the focus of nutrition science (Elzen et al, 2010;Koletzko et al, 2013;Waldmann et al, 2004).…”
Section: Health Indicators To Be Considered In the Field Of Nutritionmentioning
confidence: 99%
“…Average values for subjects were almost the same as those in controls. It is important to note that lifestyle factors, such as weight loss, diet and nutrition can affect the results of blood counts in women 12,13) . It appears therefore, that the effect of EGEE exposure on the haematopoietic system was equivocal among females within this study.…”
mentioning
confidence: 99%